Pengaruh Fungi Mikoriza Arbuskular Dalam Medium Zeolit Terhadap Pertumbuhan dan Intensitas Penyakit Bercak Daun Pada Bibit Kakao - Sariasih, Yenny; Hadisutrisno, Bambang; Widada, Jaka (Jurnal Agro Teknologi Tropika, 2012)
In Indonesia, cocoa (Theobromae cacao L.) is one of the nations third-largest contributor of foreign exchange, but the problem that arises on cocoa plantations in Indonesia is the difficulty of obtaining a healthy cacao seedlings in large numbers for the rejuvenation of cocoa cropping. One of methods to obtained healthy cacao seedlings with good performance in large numbers is application of arbuscular mycorrhizal fungi (AMF). This researches aims to observe the role of AMF mass production in the zeolite medium on the growth and leaf spot intensity of cocoa seedlings. The researches were conducted at the field condition in Sleman, Yogyakarta and Mycological Laboratory of the Faculty of Agriculture and the Laboratory of Phytochemistry, Faculty of Pharmacy, University of Gadjah Mada, Yogyakarta. The main ingredient of the study is AMF mass production in the zeolite medium. The observed variables were the growth of cocoa seedlings, the number of spores from each location, the cocoa seedlings height, leaf numbers, wet weight, dry weight and root length of seedlings of cocoa, symptom and intensity of leaf spot disease, detection of salicylic acid (SA) manually and TLC methods, and environmental factors which include: temperature, humidity and light intensity. The results indicated that the only real difference in the height and number of leaves, whereas other variables were not significantly different. This is because AMF spores from all locations are derived from the similarity of the two genera, namely Glomus sp., and Gigaspora sp., and was almost the same amount. Leaf spot disease symptoms appeared only a few of the cocoa seedlings, but more due to unfavorable environmental factors and conditions are weak pathogens. Plant defense responses had not been established because the salicylic acid content in leaves of cocoa seedlings at 12 weeks has not been detected.